(Invited) Plasma Deposition of Antibacterial Nano-Coatings on Polymeric Materials. (21st April 2017) - Nikiforov, Anton; Leys, Christophe; Kuchakova, Iryna; Vanneste, Myriam; Heyse, Pieter; De Vrieze, Mike; Zille, Andrea; Dinescu, Gheorghe; Mitu, Bogdana; Modic, Martina; Cvelbar, Uros
Abstract : Non-woven textile materials with antimicrobial properties are of high demands for applications ranging from medical dressing to everyday cleaning products. Plasma assisted route to engineer antimicrobial nano-composite coatings is proposed. Nano-particles of Ag, Cu and ZnO are tested as antimicrobial agents with average nano-particle size of 20-50 nm. Nanoparticles are incorporated in between two layers of an organosilicon film. The effect of the barrier coating on nano-particles release is determined by XPS. Antibacterial efficiency of the samples against P. aeruginosa ATCC 9027 and S. aureus M u50 bacteria shows that all treated samples exhibit higher antibacterial efficiency against S. aureus . The antibacterial efficiency of AgNPs and CuNPs is above 90% which is practically interesting for medical application while ZnONPs shows lower antibacterial efficiency.